Towards a Neurobiology of Female Aggression - Been, Laura E. (Neuropharmacology, 2018)
Although many people think of aggression as a negative or undesirable emotion, it is a normal part of many species’ repertoire of social behaviors. Purposeful and controlled aggression can be adaptive in that it warns other individuals of perceived breaches in social contracts with the goal of dispersing conflict before it escalates into violence. Aggression becomes maladaptive, however, when it escalates inappropriately or impulsively into violence. Despite ample data demonstrating that impulsive aggression and violence occurs in both men and women, aggression has historically been considered a uniquely masculine trait. As a result, the vast majority of studies attempting to model social aggression in animals, particularly those aimed at understanding the neural underpinnings of aggression, have been conducted in male rodents. In this review, we summarize the state of the literature on the neurobiology of social aggression in female rodents, including social context, hormonal regulation and neural sites of aggression regulation. Our goal is to put historical research in the context of new research, emphasizing studies using ecologically valid methods and modern sophisticated techniques.